1995
DOI: 10.1128/jvi.69.3.1959-1963.1995
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a live, attenuated human parainfluenza type 3 virus candidate vaccine strain

Abstract: Characterization of a temperature-sensitive and live, attenuated human parainfluenza type 3 virus strain (cp45) grown at a permissive temperature (32؇C) suggested that the virus efficiently multiplies in cell lines and retains antigenic and functional properties of the envelope glycoproteins. When grown at a nonpermissive temperature (39.5؇C), the cp45 virus exhibited poor replication; however, shifting to a permissive temperature allowed virus growth. Although at a nonpermissive temperature virus polypeptide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Alternatively, mutations present in a current candidate vaccine strain of HPIV-3 could be inserted into pHPIV-3. One such HPIV-3 strain was passaged serially at low temperatures and found to contain mutation(s) within the L gene that attenuate growth at 37°C (30,31). The precise mutation or mutations resulting in the attenuated phenotype are not known, but by inserting specific alterations into pHPIV-3, it should be possible to distinguish between silent mutations and the attenuating mutation(s).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, mutations present in a current candidate vaccine strain of HPIV-3 could be inserted into pHPIV-3. One such HPIV-3 strain was passaged serially at low temperatures and found to contain mutation(s) within the L gene that attenuate growth at 37°C (30,31). The precise mutation or mutations resulting in the attenuated phenotype are not known, but by inserting specific alterations into pHPIV-3, it should be possible to distinguish between silent mutations and the attenuating mutation(s).…”
Section: Discussionmentioning
confidence: 99%
“…The ts phenotype is generally associated with attenuation of virus-associated disease in host animals (18). Work on a ca, ts, attenuated candidate vaccine strain (cp45) against human parainfluenza type 3, another important cause of viral respiratory disease in the pediatric population, has shown that the ts phenotype of the virus is associated with poor transcriptional activity at the nonpermissive temperature (16,17). 2B33F and 2B20L are mutants that are both ts and ca in vitro, as well as attenuated for growth in animal models (18).…”
Section: Discussionmentioning
confidence: 99%
“…Successive passage at lower temperatures has been shown to attenuate HPIV. The most promising vaccine candidate using this approach, cp45, is designated by the number of times the virus was passaged at low temperature in African green monkey kidney cells (Belshe and Hissom, 1982;Ray et al, 1995). The vaccine was safe and immunogenic in adults, seropositive and seronegative children, and infants 1 month of age or older (Belshe et al, 2004b).…”
Section: Hpivmentioning
confidence: 99%